Learning from Tradition: Vernacular Built Heritage of Madeira (Portugal), a Sustainable Proposal - Martins, Ana Maria Tavares (2020)
The archipelago of Madeira (Portugal), of volcanic origin and situated in the intraplate region of the African plate, was formed during the Miocene and seats in a full oceanic domain. Since the settlement of the island (15th century), several destructive landslides have happened. In the Island of Madeira, housing is an important expression of the action of man over nature, thus creating a harmonious landscape between the built and its surroundings. In response to the accentuated Topography, terraced platforms appeared to soften this inclination. Vernacular building traditions are repeatedly cited in the academic literature as exemplary models of environmental practice. Therefore, research that addresses the vernacular traditions of the Island of Madeira may emphasize its potential for continuity and viability for maintenance and rehabilitation. Sustainability is indissolubly linked to vernacular architecture and the lessons learned from this architecture of the past can teach us which knowledge to apply in the future. The demand for sustainable buildings with minimal environmental impact is increasing, thus leading the construction industry to adopt new technologies for building design. Achieved for generations, this architecture shows us the art of a population in the construction. The rural housing of Madeira revealed itself as a wise design, where the masters of the craft created a perfect communion between the space, utility, comfort and the volumetric balance, thus creating a new artificial element that connects perfectly with the natural space. Passive strategies have been used around the world for centuries. In the last decades, inhabitants became dependent on mechanical systems with rising economic and environmental impacts. Learning from the past to understand how houses evolved to respond to the surrounding environment is important. The analysis of the local vernacular dwellings will provide insight into well-adapted popular solutions to deal with the local climatic conditions in order to promote responsive passive building technologies and a sustainable proposal is also presented.